Recent advances in the diagnosis and treatment of membranoproliferative glomerulonephritis with monoclonal immunoglobulin deposition - Zhang Yuan-yuan; Wang Feng-mei (Linchuang shenzangbing zazhi)
Membranoproliferative glomerulonephritis with monoclonal immunoglobulin deposition （MPGNMID） is a rare type of monoclonal gammopathy of renal significance. A definite diagnosis is largely based upon clinical features，laboratory examinations，renal biopsy and hematological evaluations. With a recently rising caseload of membranoproliferative glomerulonephritis with monoclonal IgA/IgM or light-chain deposits，new diagnostic and therapeutic advances have been summarized.